Clustering algorithm and analysis based on objective trust modeling in MANET - ZHANG Qiang; HU Guang-ming; CHEN Hai-tao; GONG Zheng-hu (Tongxin xuebao, 2009)
In mobile-adhoc networks（MANET）,an objective trust estimation model was presented,and then a maxi-mum-objective-trust-based clustering solution（MOTBCS） was raised,which aimed at the opinion of maximum stable links and energy viewpoints and gave nodes their objective trust estimation.This solution only extended the original HELLO message for the benefit of small costs and it could be better suitable for the realistic working environments in MANETs.Simulation results show that MOTBCS generate more stable clustering groups.It also has less communication costs and better efficiency than other clustering algorithms.